Effect of mistimed eating patterns on breast and prostate cancer risk (MCC‐Spain Study) - Kogevinas, Manolis; Espinosa, Ana; Castelló, Adela; Gómez‐Acebo, Inés; Guevara, Marcela; Martin, Vicente; Amiano, Pilar; Alguacil, Juan; Peiro, Rosana; Moreno, Victor; Costas, Laura; Fernández‐Tardón, Guillermo; et al. (International journal of cancer, 2018)
Modern life involves mistimed sleeping and eating patterns that in experimental studies are associated with adverse health effects. We assessed whether timing of meals is associated with breast and prostate cancer risk taking into account lifestyle and chronotype, a characteristic correlating with preference for morning or evening activity. We conducted a population‐based case‐control study in Spain, 2008–2013. In this analysis we included 621 cases of prostate and 1,205 of breast cancer and 872 male and 1,321 female population controls who had never worked night shift. Subjects were interviewed on timing of meals, sleep and chronotype and completed a Food Frequency Questionaire. Adherence to the World Cancer Research Fund/American Institute of Cancer Research recommendations for cancer prevention was examined. Compared with subjects sleeping immediately after supper, those sleeping two or more hours after supper had a 20% reduction in cancer risk for breast and prostate cancer combined (adjusted Odds Ratio [OR] = 0.80, 95%CI 0.67–0.96) and in each cancer individually (prostate cancer OR = 0.74, 0.55–0.99; breast cancer OR = 0.84, 0.67–1.06). A similar protection was observed in subjects having supper before 9 pm compared with supper after 10 pm. The effect of longer supper‐sleep interval was more pronounced among subjects adhering to cancer prevention recommendations (OR both cancers= 0.65, 0.44–0.97) and in morning types (OR both cancers = 0.66, 0.49–0.90). Adherence to diurnal eating patterns and specifically a long interval between last meal and sleep are associated with a lower cancer risk, stressing the importance of evaluating timing in studies on diet and cancer. What's new? Evidence shows that long‐term disruption of endogenous circadian rhythms may be associated with cancer. The effects of mistimed sleeping and eating patterns that come with modern life are however less clear. This large Spanish population‐based study examined whether meal timing and sleep patterns are associated with the two most common nightshift‐related cancers. Adherence to a more diurnal eating pattern, and specifically an early supper and a long interval between last meal and sleep were associated with a lower breast and prostate cancer risk, stressing the importance of evaluating circadian rhythms in diet and cancer studies and revisiting recommendations for prevention.